Business Intelligence Dashboard Lokasi Rawan Bencana Alam Di Indonesia Menggunakan Tableau - Faurika, F; Haris, M Syauqi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Natural disasters cause socio-economic damage in a country. Indonesia is one of the countries prone to being affected by natural disasters. This disaster was triggered by various factors, both natural factors and human factors themselves that did not protect the natural ecosystem. This research aims to visualize data on natural disaster cases in Indonesia that occurred in the period 2020 to 2023. This visualization of natural disasters in Indonesia applies Business Intelligence (BI) using Tableau Public to produce information from a dataset of natural disaster cases in Indonesia for the period 2020 to 2023 in the form of visuals to facilitate the process of analyzing natural disaster cases in Indonesia and with an attractive visual appearance. The results of the visualizations obtained in this research are combined to form an attractive dashboard and contains visual information on the distribution of disasters in various provinces in Indonesia, the number of disasters that occurred, the number of victims, the amount of damage, and disaster trends from 2020 to 2023.